2022
DOI: 10.3389/fnut.2022.939571
|View full text |Cite
|
Sign up to set email alerts
|

Dietary compounds in modulation of gut microbiota-derived metabolites

Abstract: Gut microbiota, a group of microorganisms that live in the gastrointestinal tract, plays important roles in health and disease. One mechanism that gut microbiota in modulation of the functions of hosts is achieved through synthesizing and releasing a series of metabolites such as short-chain fatty acids. In recent years, increasing evidence has indicated that dietary compounds can interact with gut microbiota. On one hand, dietary compounds can modulate the composition and function of gut microbiota; on the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 197 publications
(164 reference statements)
0
11
0
Order By: Relevance
“…Another large retrospective study confirmed that increased adherence to the Mediterranean diet and PBD mitigates the loss of gut microbiome diversity, reduces frailty, metabolic disorders, and inflammatory aging, 311 , 312 and suppresses gut‐dependent metabolites associated with high cardiometabolic risk, such as trimethylamine‐N‐oxide (TMAO). 313 , 314 …”
Section: Potential Mechanism Mediating the Effects Of Dietary Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another large retrospective study confirmed that increased adherence to the Mediterranean diet and PBD mitigates the loss of gut microbiome diversity, reduces frailty, metabolic disorders, and inflammatory aging, 311 , 312 and suppresses gut‐dependent metabolites associated with high cardiometabolic risk, such as trimethylamine‐N‐oxide (TMAO). 313 , 314 …”
Section: Potential Mechanism Mediating the Effects Of Dietary Patternsmentioning
confidence: 99%
“…Another large retrospective study confirmed that increased adherence to the Mediterranean diet and PBD mitigates the loss of gut microbiome diversity, reduces frailty, metabolic disorders, and inflammatory aging, 311,312 and suppresses gut-dependent metabolites associated with high cardiometabolic risk, such as trimethylamine-N-oxide (TMAO). 313,314 From the above review of recent evidence, it is easy to conclude that dietary patterns can participate in various aspects of metabolic regulation by shaping the gut microbiome, as shown in Table S3. Gut microbiota can also influence host metabolic phenotypes by inversely affecting appetite and dietary preferences.…”
Section: Gut Microbiota and Its Metabolitesmentioning
confidence: 99%
“…Dietary compounds with low bioavailability or that cannot be absorbed directly [ 76 ], pass the small intestine and enter the colon, where they will interact with live gut bacteria [ 31 ]. The colon is the ideal place for the interactions between the intestinal microbiota and the dietary compounds since, in addition to a high level and diversity of the microorganisms present, it supplies the suitable pH and time for direct contact between microbes and food [ 67 ].…”
Section: Intestinal Microbiota Metabolitesmentioning
confidence: 99%
“…Diet is one of the most important regulators of the intestinal microbiota [ 31 ], but there is a lack of information about the relationship between carotenoids and the intestinal microbiota [ 32 ]. In addition to that, these natural pigments are hydrophobic molecules, which makes their solubility in water low and, when exposed to light, heat, oxygen, or acids, are very susceptible to multiple oxidation and isomerisation reactions [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, microbial SCFAs producers have been reported to generally possess a vast repertoire of metabolic pathways, not limited only to energy-related metabolism (i.e., short-chain fatty acid synthesis) but also including enzymes for amino acid and vitamin metabolism as well as for the synthesis of other by-products [20,21].…”
Section: Introductionmentioning
confidence: 99%